The Influence of Emotional Intelligence on Auditor Performance - Richard G. Brody; Gaurav Gupta; Stephen B. Salter (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: How does Emotional Intelligence influence auditor performance? Motivation - Emotional Intelligence has been researched as one of the critical factors that are linked to superior work performance. However, this research is still in its infancy with respect to auditors despite the fact that the auditing profession would benefit greatly from improving the work performance of its professionals. In this paper, we address this issue and lay the foundation for a future paper that would analyze the impact of increasing the emotional intelligence of auditors on their task performance. We hypothesized that emotional intelligence is positively related to auditor performance. Data - Undergraduate accounting and MBA students were selected to participate in this study. Sixty-nine participants completed the Emotional Intelligence inventory provided by Genos International, Australia and performed a simple audit activity designed by the authors for this study. Multiple regressions were utilized to analyze the data. Findings - The hypothesis was not supported, and the paper addresses this result as well as provides guidance to future researchers in this significant area. Contribution: Because of the challenges associated with this type of experiment as well as the lack of existing research in the area, this paper uses student subjects to provide initial feedback on the effectiveness of the instrument. The results will help guide future research and, as an added benefit, preserves the subject pool of practicing auditors.
Keywords: M41; 650; Emotional Intelligence; Auditor Performance; Genos International Inventory